‘When you own the time, it’s seamless, but when you don’t, it’s horrific’: critical, public order and major incident decision-making in policing - Huey, Laura (Policing and society, 2024)
On 24 May 2022, a gunman entered an elementary school in Uvalde, Texas and fatally shot 19 victims. During the incident, local police were present at the site but did not enter the building to confront the gunman. It was subsequently reported that an Incident Commander mischaracterised the situation as a ‘barricaded subject’ rather than as an ‘active shooter’, and officers were ordered to stay out of the scene and to keep student families and bystanders from entering the building. Drawing on qualitative interviews with Incident Commanders, Critical Incident Commanders, Emergency Planners, and Tactical and Public Order Unit personnel, our research seeks to better understand the influence of various stressors on decision-making in high-risk, high-profile events. This paper presents an analysis of these interviews that considers four important questions: 1. Who becomes an IC? 2. What is the function of an IC during a major, critical, and public order incident? 3. What factors influence IC decision-making? and 4. What are the sources of stress involved in IC decision-making and work?